Kewarganegaraan Sebagai Syarat Kepemilikan Tanah: Telaah Filosofis dan Yuridis - Miftahul Jannah; Nabila Putri Fauziyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Land ownership in Indonesia has both philosophical and juridical dimensions closely linked to citizenship status. According to the Basic Agrarian Law (UUPA) of 1960, only Indonesian citizens are entitled to hold full ownership rights over land. This study aims to analyze the philosophical and juridical foundations of citizenship as a prerequisite for land ownership and its implications for social justice and national sovereignty. The research employs a normative legal method with statutory, conceptual, and philosophical approaches. Data are obtained through literature review of legislation, court decisions, and scholarly works, including Ahmad Muhammad Mustain Nasoha’s views on citizenship in the agrarian law context. The results indicate that restrictions on foreign land ownership are not merely administrative policies but a philosophical manifestation of the idea that land is essential to state sovereignty and public welfare. Juridically, this regulation reinforces the principles of nationality and distributive justice within Indonesia’s agrarian legal system. The study concludes that citizenship as a requirement for land ownership functions as a legal safeguard of the nation’s right to the land and a means to achieve social justice.